Florida Poly Primers: Calculus. Issue 7 (9th August 2018) - Kindle, Jennifer; Gentimis, Thanos
Abstract: At Florida Polytechnic University, a STEM University founded in 2014, Calculus I is the first mathematics course required by students in every major. In order to ensure students received the support necessary for Calculus I, an online Primer course was developed. The course, which is housed in the online platform CANVAS, targets specific topics and skills necessary for students to achieve success in Calculus I. In this paper, we present the positive effect of the Primer on the retention rate for Calculus I, on pass rate, and on average grade received.